Advances in global leadership. Vol. 4 - Mobley, William H.; Weldon, Elizabeth (Emerald, 2005)
The seven chapters in Part 1, of this volume, focus on the foundations of global leadership. Together, these chapters explore a broad selection of the social and psychological processes underlying effective global leadership. These authors expand ideas currently in use, and they introduce new ideas for our consideration. The seven papers in Part 2 focus on the practice of global leadership. Compared to those in Part 1, these chapters focus more on practical solutions to the problems that leaders face than the analysis of fundamental processes, although this distinction is one of degree. All the authors in Part 1 explore the practical implications of their ideas, and those in Part 2 contribute to the development of fundamental concepts. It provides analysis on the foundation of global leadership principles. It discusses practical solutions to the problems faced by today's global leaders. It offers an international representation.
Keywords: Leadership.; Executive ability.; elektronické knihy; electronic books